PENGARUH MOTIVASI KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA PT. WIRASTUTI KABUPATEN SIAK - Alri Yogi; Lena Farida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The research was conducted at PT. Wirastuti Siak with the aim to analyzethe effect of work motivation on employee performance at PT. Wirastuti Siak.Variable in this research is the motivation to work (independent variable) andperformance (the dependent variable). The sample in this study is as much as 55employees by using census techniques. The analytical method used is a simpleregression analysis. The result showed that the analysis of employee motivation atPT. Wirastuti Siak in the category Good with a score of 1,712 acquisition.Analysis of employee performance at PT. Wirastuti Siak was in good categorywith the acquisition of a score of 2,135. There are Work Motivation Effect AgainstEmployee achievement using the coefficient of determination is KD = r 2 x 100%= (0446) 2 x 100% = 0199 means that the average value of 19.9% of workmotivation is determined by job performanceKeywords: Work Motivation, Job Performance